2013
DOI: 10.2147/ijwh.s51403
|View full text |Cite
|
Sign up to set email alerts
|

Association between vitamin D insufficiency and adverse pregnancy outcome: global comparisons

Abstract: BackgroundVitamin D insufficiency has been associated with a number of adverse pregnancy outcomes, and has been recognized as a public health concern.AimThe objective of this study was to determine the impact of vitamin D deficiency on maternal complications like gestational diabetes mellitus (GDM), anemia, iron deficiency, and preeclampsia among pregnant women.Subjects and methodsThis was a cohort study undertaken at antenatal clinics at the Women’s Hospital of Hamad Medical Corporation in Doha. A total of 2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
80
4
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(95 citation statements)
references
References 39 publications
9
80
4
2
Order By: Relevance
“…This was also observed by Bener, et al; [10] where the risk of vitamin D deficiency was higher among young pregnant women below 30 years old and Bowyer, et al [11] in Australia where younger maternal age was associated with lower maternal serum 25-OHD (≤ 25 nmol/l) [(OR, 95% CI) 0·93 (0·89-0·97, P = 0·001)]. However, Maghbooli, et al; [16] and El koumi, et al; [23] found no significant correlation between maternal serum vitamin D concentration with age (P = 0.2).…”
Section: Resultssupporting
confidence: 84%
“…This was also observed by Bener, et al; [10] where the risk of vitamin D deficiency was higher among young pregnant women below 30 years old and Bowyer, et al [11] in Australia where younger maternal age was associated with lower maternal serum 25-OHD (≤ 25 nmol/l) [(OR, 95% CI) 0·93 (0·89-0·97, P = 0·001)]. However, Maghbooli, et al; [16] and El koumi, et al; [23] found no significant correlation between maternal serum vitamin D concentration with age (P = 0.2).…”
Section: Resultssupporting
confidence: 84%
“…Total physical activity significantly correlated with severe vitamin D deficiency, which has been shown in previous studies of pregnant women in other countries (47,48). This correlation is observed because physical activity levels reflect the amount of exposure to sunlight in some degree.…”
Section: Discussionsupporting
confidence: 77%
“…Higher rates of severe vitamin D deficiency were previously reported in the literature from Turkey 10,17 . Those prior studies have shown that covered dress style may be an important factor affecting the prevalence of vitamin D deficiency in Muslim populations due to the religious and cultural reasons 10,18. The prevalence of low vitamin D levels was greater in cases which were sampled in winter, in women who had limited access to sunlight, those living in countries at higher latitudes and those with higher skin pigmentation 16,[18][19][20] . In a study by Perez et al, 21 it was observed that only 35.9% of pregnant women in the first trimester had adequate serum 25(OH)D levels (≥30 ng/mL) and non-Caucasian ethnicity, season at sampling (autumn/winter) and nulliparity were found to be associated with 25(OH)D deficiency.…”
Section: Discussionmentioning
confidence: 93%